Psychological Stress, Intestinal Barrier Dysfunctions, and Autoimmune Disorders: An Overview - Ilchmann-Diounou, Hanna (Front Immunol, 2020)
Autoimmune disorders (ADs) are multifactorial diseases involving, genetic, epigenetic, and environmental factors characterized by an inappropriate immune response toward self-antigens. In the past decades, there has been a continuous rise in the incidence of ADs, which cannot be explained by genetic factors alone. Influence of psychological stress on the development or the course of autoimmune disorders has been discussed for a long time. Indeed, based on epidemiological studies, stress has been suggested to precede AD occurrence and to exacerbate symptoms. Furthermore, compiling data showed that most of ADs are associated with gastrointestinal symptoms, that is, microbiota dysbiosis, intestinal hyperpermeability, and intestinal inflammation. Interestingly, social stress (acute or chronic, in adult or in neonate) is a well-described intestinal disrupting factor. Taken together, those observations question a potential role of stress-induced defect of the intestinal barrier in the onset and/or the course of ADs. In this review, we aim to present evidences supporting the hypothesis for a role of stress-induced intestinal barrier disruption in the onset and/or the course of ADs. We will mainly focus on autoimmune type 1 diabetes, multiple sclerosis and systemic lupus erythematosus, ADs for which we could find sufficient circumstantial data to support this hypothesis. We excluded gastrointestinal (GI) ADs like coeliac disease to privilege ADs not focused on intestinal disorders to avoid confounding factors. Indeed, GIADs are characterized by antibodies directed against intestinal barrier actors.